2005
DOI: 10.1140/epjb/e2005-00293-1
|View full text |Cite
|
Sign up to set email alerts
|

Spin glass models with ferromagnetically biased couplings on the Bethe lattice: analytic solutions and numerical simulations

Abstract: We derive the zero-temperature phase diagram of spin glass models with a generic fraction of ferromagnetic interactions on the Bethe lattice. We use the cavity method at the level of one-step replica symmetry breaking (1RSB) and we find three phases: A replica-symmetric (RS) ferromagnetic one, a magnetized spin glass one (the so-called mixed phase), and an unmagnetized spin glass one. We are able to give analytic expressions for the critical point where the RS phase becomes unstable with respect to 1RSB soluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 24 publications
(47 reference statements)
4
67
1
Order By: Relevance
“…The result is shown in figure B1 where the spin-glass susceptibility diverges below this line. At zero temperature, the critical probability is calculated as p c = 11/12 in [27,32], which is reproduced by our numerical calculation at zero temperature as p c = 0.916 65 (5).…”
Section: Appendix B the Critical Condition Based On The Spin-glass Ssupporting
confidence: 72%
See 1 more Smart Citation
“…The result is shown in figure B1 where the spin-glass susceptibility diverges below this line. At zero temperature, the critical probability is calculated as p c = 11/12 in [27,32], which is reproduced by our numerical calculation at zero temperature as p c = 0.916 65 (5).…”
Section: Appendix B the Critical Condition Based On The Spin-glass Ssupporting
confidence: 72%
“…Indeed, it is suggested that the spin-glass phase in the RRG has the full RSB [27,28]. However, we should be careful because we have not directly seen the instability of a replica-symmetric solution in the Bethe lattice of our definition.…”
Section: Behaviour Of the Two-dimensional Distribution Of Zerosmentioning
confidence: 85%
“…So on the right of the cusp we have an unmagnetised spin glass phase, while on the left we have a mixed phase, i. e. spin glass with nonzero magnetization, usual for disordered systems with a directional bias in the couplings or in the external field. It is worth reminding that the location of this phase transition is only approximate, as one should use an ansatz with RSB in order to compute it exactly [46].…”
Section: Extrapolation In Qmentioning
confidence: 99%
“…57 Its presence has been confirmed in the ±J Ising model on a Bethe lattice. 58 However, there is no evidence of a mixed phase in the ±J Ising model on a cubic lattice 55 and in related models. 59 In particular, the numerical results of Ref.…”
Section: Ising Spin Glass Systems a The ±J Edwards-anderson Isinmentioning
confidence: 99%